2005
DOI: 10.1007/s10591-005-4040-8
|View full text |Cite
|
Sign up to set email alerts
|

Premature termination as a function of intake data based on ethnicity, gender, socioeconomic status, and income

Abstract: Although it is acknowledged that premature termination is detrimental to the therapy process, there is limited information on how to utilize client demographic data to indicate which clients have greatest potential to prematurely terminate. The study assessed how client ethnicity interacts with client gender, therapist gender, therapist ethnicity, and client socioeconomic status (education and income) to affect premature termination. The study consisted of 527 cases which received therapy services from the Aub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…We found that these variables effected therapists similarly, i.e., there were no random slopes. For dropout, the patient variables identified were similar to those reported elsewhere: greater symptom severity at intake (Kazdin et al, 1994); younger age (e.g., Edlund et al, 2002), and non-white ethnicity and unemployment, which may be proxy measures of socioeconomic deprivation (Garfield, 1994;Wierzbicki & Pekarik, 1993;Williams, Ketring & Salts, 2005). In addition, and possibly of greater concern, was the finding that patients at risk of harming themselves or others were more likely to dropout than patients with no risk, a finding that supports previous research from a single service study using CORE risk items (Saxon, Ricketts, & Heywood, 2010).…”
Section: Case-mix Variablesmentioning
confidence: 59%
“…We found that these variables effected therapists similarly, i.e., there were no random slopes. For dropout, the patient variables identified were similar to those reported elsewhere: greater symptom severity at intake (Kazdin et al, 1994); younger age (e.g., Edlund et al, 2002), and non-white ethnicity and unemployment, which may be proxy measures of socioeconomic deprivation (Garfield, 1994;Wierzbicki & Pekarik, 1993;Williams, Ketring & Salts, 2005). In addition, and possibly of greater concern, was the finding that patients at risk of harming themselves or others were more likely to dropout than patients with no risk, a finding that supports previous research from a single service study using CORE risk items (Saxon, Ricketts, & Heywood, 2010).…”
Section: Case-mix Variablesmentioning
confidence: 59%
“…One potential goal is to investigate empirical relationships between a diversity issue and a defined outcome. For example, researchers have analyzed how diverse social identities relate to such clinically relevant variables as the perceived effectiveness of therapy techniques (Cline, Mejia, Coles, Klein, & Cline, 1984) and premature termination (Williams, Ketring, & Salts, 2005). The relationship between diverse social identities and nontherapeutic outcomes has also been analyzed (e.g., Barnett, Del Campo, Del Campo, & Steiner, 2003).…”
Section: The Goals and Objectives Of Studying Diversity Social Justimentioning
confidence: 99%
“…On the other hand, a number of students who do seek help at a counseling center terminate counseling prematurely (Hatchett & Park, 2003;Hunsley, Aubry, Verstervelt, & Vito, 1999). Predictors of premature termination are client demographics, diagnosis, quality of working alliance, and counselor power (Williams, Ketring, & Salts, 2005;Woodside, Carter, & Blackmore, 2004). Of particular concern, Lucas & Hunt (2001) and Lucas & Berkel (2005) reported that clients who terminated counseling prematurely reported at their intake session a greater degree of nervousness, tenseness, and worry than those who completed counseling.…”
Section: S Lucasmentioning
confidence: 99%